A Kentucky Christmas - Lyon, George Ella, 1949- (University Press of Kentucky, 2003)
A celebration of holiday poetry, fiction, essays, recipes, and songs by more than sixty of the Bluegrass state's finest writers. Gathered here are writings from some of the legendary voices of Kentucky -- and the nation -- as well as original Christmas stories and poetry from some of the state's emerging talents. Among the contributors to this handsome collection are Kentucky's visionaries, storytellers, historians, singers, cooks, children's authors, and poets, including all five Kentucky Poet Laureates. A delight for anyone interested in Kentucky literature, history, or traditions, A Kent.